2006
DOI: 10.1021/es0523542
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ultraviolet Absorbance, Chemiluminescence, and DOAS Instruments for Ambient Ozone Monitoring

Abstract: This paper evaluates the accuracy of ozone measurements made by monitors that determine ozone concentrations in ambient air by UV absorption. These monitors are typically used to measure ozone for the purpose of establishing local compliance to air-quality standards. The study was predicated by the concern that commercially available UV absorbance O 3 monitors may be subject to interference from volatile organic carbon (VOC) species that absorb light at 254 nm. To test for these and other effects, we compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 10 publications
1
37
0
Order By: Relevance
“…The most widely used instrumental technique for the measurement of tropospheric ozone is by UV absorption (Williams et al, 2006). Ozone UV absorption monitors operate on the principle of ozone absorbing UV light at wavelengths of around 254 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used instrumental technique for the measurement of tropospheric ozone is by UV absorption (Williams et al, 2006). Ozone UV absorption monitors operate on the principle of ozone absorbing UV light at wavelengths of around 254 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Gas-phase CI instruments are more complex and are based on the reaction of ozone with either ethene or nitrogen oxide (Ridley et al, 1992;Hegglin et al, 2006;Williams et al, 2006;Bariteau et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Leston et al 5 reported substantial differences between collocated UV and chemiluminescence measurements during peak O 3 periods in a polluted urban setting. On the other hand, Williams et al 18 found good agreement among UV, chemiluminescence (O 3 -NO), and differential optical absorption spectroscopy (DOAS) O 3 measurements at an urban site and a suburban/industrial location. They also compared the UV and chemiluminescence methods during sampling aboard ship in polluted and clean air.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies 5,[17][18][19] have compared O 3 measurements made in ambient air by different instruments. Leston et al 5 reported substantial differences between collocated UV and chemiluminescence measurements during peak O 3 periods in a polluted urban setting.…”
Section: Introductionmentioning
confidence: 99%